SHAPE MEMORY ALLOYS:A REVIEW - Prajakta Gaikwad; M. A. Sayeed; Aishwarya Sonkamble (International Journal of Innovations in Engineering Research and Technology, 2021)
Nowadays along with conventional metals or materials, there is a need of smart materials in the industries. Shape memory alloys (SMAs) are considered as smart materials. They have been used for a wide variety of applications in various fields like aircraft, aerospace, medicine, telecommunication, etc. This paper consists of a review on “Shape memory alloys”. The unique behavior of SMAs is being discussed in this paper thoroughly. This paper includes the characteristic properties of shape memory alloys along with Shape memory effect, brief introduction of SMAs, its crystal structure and its applications are also explained in detail.